PENGEMBANGAN INSTRUMEN PENELITIAN UNTUK MENGUKUR KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIDK DI SEKOLAH DASAR - Hafiziani Eka Putri; Bening Cipta Alam; Puji Rahayu; Afridha Laily Alindra; Nenden Permas Hikmatunisa; Fitri Nuraeni; Nopi Krisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' mathematical connection ability is a crucial skill to master. However, research indicates that this ability is still low in elementary schools. Therefore, the researcher is interested in conducting this study to develop an instrument as a measurement tool for students' mathematical connection ability in elementary schools. This research employs a Research & Development (R&D) method with a sample of 44 sixth-grade students selected using purposive sampling. The developed instrument consists of seven essay questions tailored to the indicators of mathematical connection ability. These questions were developed based on expert advice and underwent validity, reliability, difficulty level, and item discrimination tests. The results of this study indicate that three questions can be perfectly used as research instruments, namely questions number 2, 5, and 7, with a validity test result of 0.88 and a reliability test result of 0.93. The difficulty level of all questions is in the medium category. The item discrimination of question 2A is 54.17% (very good), 2B is 37.50% (good), 5A is 83.33% (very good), 5B is 66.67% (very good), 7A is 58.33% (very good), and 7B is 83.33% (very good). Thus, these three questions can serve as an instrument to measure the mathematical connection ability of fifth-grade elementary school students on the topic of plane figures.